A MONOGRAPH OF THE GENUS HERITIERA* Aiton** (StercuL) (including Argyrodendron F. v. M. and Tarrietia Bl.) - A. J. G. H. KOSTERMANS (Research Center for Biology, 1959)
1. The genera Heritiera Ait., Argyrodendron F.v.M. and Tarrietia Bl. are united.2. The genus comprises 29 species ranging from India, Malaysia, New Guinea and the Pacific region to tropical Australia (2 species, of which one extends to Celebes) and 2 species in tropical Africa.3. The following ten species are described here for the first time: Heritiera arafurensis Kosterm., H. aurea Kosterm., H. burmensis Kosterm., H. catappa Kosterm,H. cordata Kosterm., H. globosa Kosterm., H. macroptera Kosterm., H. novoguineensis Kosterm, H. percoriacea Kosterm., and H. pterospermoides Kosterm.4. The following ten new combinations are created: Heritiera actinophylla (Bailey) Kosterm. (basionym: Tarrietia actinophylla Bailey), H. albiflora (Ridley) Kosterm. (basionym: Tarrietia albiflora Ridley), H. borneensis (Merr.) Kosterm. (basionym: Tarrietia borneensis Merr.), H. densiflora (Pellegrin) Kosterm. (basionym: Tarrietia densiflora (Pellegrin) Aubreville et Normand), H. jaranica (Bl.) Kosterm. (basionym: Tarrietia javanica Bl.), H. kiinstleri (King) Kosterm. (basionym: Tarrietia kunstleri King), H. peralata (Domin) Kosterm. (basionym: Tarrietia peralata Domin), H. simplicifolia (Mast.) Kosterm. (basionym: Tarrietia simplicifolia Mast.), H. sumatrana (Miq.) Kosterm. (basionym: Tarrietia sumatrana Miq.), and H. trifoliolata (F.v. M.) Kosterm. (basionym: Argyrodendron trifoliolatum F. v. M.).5. The following fifteen species are reduced to synonymy: Argyrodendron amboinensis Haberlandt; Heritiera acuminata Wall, ex Kurz, H. annamensis Lecomte,H. minor Lam. H. tothila (Gaertn.) Kurz, H. vespertilio Kurz; Tarrietia actinodendron Guilfoyle, T. amboinensis Hochr, T. Argyrodendron Benth., T. carroni Moore, T. curtisii King, T. perakensis King, T. riedeliana Oliv., T. rubiginosa Kosterm. and T. - unifoliolata Ridley. 6. The following seven species are excluded from the genus: Heritiera attenuata Wall., H. grandis Fisch. ex Steud., H. spectabilis Baill., H. tinctoria Blanco; Tarrietia barteri (Mast.) Hochr., T. erythrosiphon (Baill.) Hochr. and T. perrieri Hochr,